Management and treatment of femoral neck stress fractures in recreational runners: a report of four cases and review of the literature - Biz, Carlo; Berizzi, Antonio; Crimì, Alberto; Marcato, Chiara; Trovarelli, Giulia; Ruggieri, Pietro (Acta Biomedica Atenei Parmensis, 2017)
Femoral neck stress fractures (FNSFs) in healthy young subjects are uncommon and most prevalent among long-distance runners and military recruits. Women seem to be at higher risk of developing stress fractures because of possible eating disorders followed by amenorrhea and osteoporosis. This case report describes four young and middle-aged, active female recreational runners who developed stress fractures of the femoral neck. In three of them, with a clinical history of persistent pain in the groin region, which worsened during training, early diagnosis by MRI was considered essential in detecting the fractures. The patients were clinically, metabolically and radiographically evaluated; they were then treated and followed-up at our institution. Only one case was treated conservatively, while the others underwent surgical internal fixation using a screw-plate (DHS®). All of them returned to sport physical activity after a recovery period. Regarding the challenging management of FNSFs, our report highlights the importance of groin pain, especially in athletic females, an early diagnosis by MRI, and a proper classification of these injuries for a correct choice of treatment in order to prevent further dislocation and avoid avascular necrosis of the femoral head.